Defending the land of the jaguar : a history of conservation in Mexico - Simonian, Lane, 1960- (University of Texas Press, 1995)
Mexican conservationists have sometimes observed that it is difficult to find a country less interested in the conservation of its natural resources than is Mexico. Yet, despite a long history dedicated to the pursuit of development regardless of its environmental consequences, Mexico has an equally long, though much less developed and appreciated, tradition of environmental conservation. Lane Simonian here offers the first panoramic history of conservation in Mexico from pre-contact times to the current Mexican environmental movement. He explores the origins of conservation and environmental concerns in Mexico, the philosophies and endeavors of Mexican conservationists, and the enactment of important conservation laws and programs. This heretofore untold story, drawn from interviews with leading Mexican conservationists as well as archival research, will be important reading throughout the international community of activists, researchers, and concerned citizens interested in the intertwined issues of conservation and development.